2017
DOI: 10.4149/neo_2017_111
|View full text |Cite
|
Sign up to set email alerts
|

Late cardiac effect of anthracycline therapy in physically active breast cancer survivors – a prospective study

Abstract: The late-onset cardiotoxic effect of anthracycline is known, however the early detection and prevention of subclinical myocardial damage has not been fully understood yet. Besides medical therapy regular physical activities may also play a role in the prevention and reduction of side effects of chemotherapy. The aim of our present study was to detect the effect of regular physical activities on the diastolic function and on the symptoms of late heart failure in case of anthracycline chemotherapy. The prospecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…Studies have shown fewer CV events in cancer patients who exercise on a regular basis. In a prospective analysis of 55 females with breast cancer who received anthracycline therapy, were 65 or younger, and had no CV risk factors, there were fewer symptoms of heart failure in physically active patients over a 5-year follow-up period [66]. There was also a delayed onset of diastolic dysfunction compared to inactive patients [66].…”
Section: Lifestyle Modificationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown fewer CV events in cancer patients who exercise on a regular basis. In a prospective analysis of 55 females with breast cancer who received anthracycline therapy, were 65 or younger, and had no CV risk factors, there were fewer symptoms of heart failure in physically active patients over a 5-year follow-up period [66]. There was also a delayed onset of diastolic dysfunction compared to inactive patients [66].…”
Section: Lifestyle Modificationsmentioning
confidence: 99%
“…In a prospective analysis of 55 females with breast cancer who received anthracycline therapy, were 65 or younger, and had no CV risk factors, there were fewer symptoms of heart failure in physically active patients over a 5-year follow-up period [66]. There was also a delayed onset of diastolic dysfunction compared to inactive patients [66]. In another, larger prospective analysis of 2973 nonmetastatic breast cancer participants with an 8.6 year median follow-up, routine exercise of ≥9 MET-hour/week was associated with a reduction in CV events (new diagnosis of coronary artery disease, valve abnormality, arrhythmia, stroke, or CVD death) [67].…”
Section: Lifestyle Modificationsmentioning
confidence: 99%
“…8 There are limited prospective data on the associations between self-reported physical activity and changes in echocardiographic measures of systolic and diastolic function with breast cancer therapy. 9 In this cohort, we had previously defined both the changes in left ventricular systolic and diastolic function with exposure to cancer therapy, which are on the order of LVEF −6.6% (95% CI, −8.2, −5.0%), longitudinal strain 0.9% (95% CI, 0.3, 1.5%), E/e′ 0.8 (0.3, 1.4) for sequential doxorubicin and trastuzumab. 3,10 Here, we performed a detailed analysis of the changes in self-reported physical activity in a well-phenotyped cohort of 603 participants with breast cancer undergoing doxorubicin and/or trastuzumab therapy to determine: (a) changes in self-reported physical activity with cancer treatment; (b) baseline predictors of physical activity during and after cancer treatment; and (c) the associations between baseline self-reported physical activity and changes in echocardiography-derived parameters of systolic and diastolic function after cancer therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Exposure to exercise training before cancer diagnosis is associated with a 20-37% risk reduction of adverse cardiovascular events in patients with primary breast cancer [11]. However, while these evidences demonstrate that regular physical activity in cancer patients improve both oncological and cardiovascular outcomes [11][12][13][14], current literature still lacks of randomized clinical trials and stronger evidence in terms of modalities, duration, intensity and timing of exercise realization with regard to cancer treatment.…”
Section: Introductionmentioning
confidence: 99%